Agroecosistemas del pacífico norte colombiano: una indagación sobre el bienestar desde el conocimiento etnobiológico de las comunidades rurales de Nuquí (Chocó) (2021)
In the north Pacific coast of Colombia, rural communities have traditionally consolidated an ethnobiological knowledge that is putting into practice in agroecosystems. Using a qualitative methodological design, this paper uses the theoretic and methodological approach of social wellbeing to examine the contribution of ethnobiological knowledge, related to traditional agroecosystems, to the wellbeing of rural communities in Nuquí (Chocó). Although there have been economic and social changes that have discouraged agriculture in the municipality, wellbeing is locally constituted as the agroecosystems allow access to a wide variety of natural resources, incorporate agroecological practices, and sustain social relations framed in diverse values and perceptions. This research contributes to the strengthening of traditional ecological knowledge and the management of the territory from local visions facilitating alternatives to development.